Peranan Teknologi Sistem Informasi dalam Penyusunan Anggaran pada Pemerintah Daerah Provinsi Sulawesi Tengah - Resky Oktaviani Sultan; Adinda Maharani; Indah Suci Rahmadani; Nina Yusnita Yamin; Betty Betty; Andi Chairil Furqan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research examines the role of information systems technology in budget planning processes at the Central Sulawesi Provincial Government, specifically analyzing the Regional Government Information System (Sistem Informasi Pemerintahan Daerah/SIPD) implementation since 2021. Using a qualitative descriptive research design with purposive sampling, this study interviewed eight informants from six key agencies (BPKAD, BAPPEDA, BPSDM, BPPID, and DISDUKCAPIL) and conducted direct observations of the budget formulation process. The findings reveal that SIPD significantly enhances budgeting efficiency through automated validation, integrated planning-finance data, and real-time monitoring capabilities. However, implementation effectiveness remains constrained by technical challenges including unstable network infrastructure, incomplete system features, organizational obstacles such as dual-system operations and limited operator capacity, and human resource gaps including competency variations and inadequate continuous training. Despite these constraints, SIPD has positively impacted budget transparency, strengthened accountability through comprehensive audit trails, and improved data quality standards. The study concludes that sustained success requires balanced improvements across three dimensions technology infrastructure enhancement, organizational governance strengthening, and systematic human capacity development to fully realize the system's potential for evidence-based budgeting and public financial management in regional government contexts.